Spatial orientation by quantum telepathy - Bovino, F; Giardina, M; Svozil, K; Vedral, V (2007)
We implemented the protocol of entanglement assisted orientation in the space proposed by Brukner et al. (quant-ph/0509123). We used min-max principle to evaluate the optimal entangled state and the optimal direction of polarization measurements which violate the classical bound. © 2007 World Scientific Publishing Company.